Pollution, economic development and democracy: Evidence from the MENA countries - Mohammad Reza Farzanegan; Gunther Markwardt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
The Middle East and North Africa (MENA) countries are among the world's top emitters of CO2 and SO2 in per capita terms. The objective of this paper is to analyze whether investing in the democratic development of these countries is an effective tool to make the economic growth in this region more environmentally compatible. Arguing on the basis of the Environmental Kuznets Curve hypothesis and using panel data on the income-emission-democracy nexus, we find evidence that improvements in the democratic development of the MENA countries help to mitigate environmental problems. Our results clearly show, that the quality of democratic institutions has a greater in uence on local environmental problems than on global environmental issues in the MENA region.
Keywords: Q56; Q58; 330; democratic development; political institutions; environmental quality; MENA; Luftverunreinigung; Kohlendioxid; Schwefeldioxid; Demokratisierung; Environmental Kuznets Curve; MENA-Staaten